Applicability of Sc2O3 versus Al2O3 in MIM rectifiers for IR rectenna. (October 2021) - Almalki, S.; Tekin, S.B.; Sedghi, N.; Hall, S.; Mitrovic, I.Z.
Abstract: Impedance matching between the terahertz antenna and ultra-fast Metal-Insulator-Metal (MIM) diode is a crucial issue in realizing rectenna technology for harvesting infrared (IR) energy spectrum. In this paper, scandium oxide (Sc2 O3 )-based MIM diodes were fabricated using magnetron sputtering and their rectification performance compared to state-of-the-art Au/Al2 O3 /Au diodes. The fabricated Al/Sc2 O3 /Al diode has exhibited around two orders of magnitude lower zero-bias dynamic resistance ( RD0  = 956 kΩ) and high zero-bias responsivity ( β0  = 1 A/W) in advance to Au/Al2 O3 /Au diode. The results point to applicability of scandium oxide in MIM rectifiers for IR rectenna.